1995
DOI: 10.1021/ma00128a046
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Two-Dimensional Morphology at Surface-Functionalized Polyethylene Films

Abstract: Polyethylene simultaneously functionalized with both pyrene labels and amine quencher groups has been studied to determine the extent to which self-organization and segregation of functional groups occurred during formation of a surface-bifunctionalized polymer. By measuring pyrene fluorescence in the presence of a surface-bound amine quencher, pyrene fluorescence after the surface bound quenchers had been protonated, and the total amount of polymer-bound pyrene based on the amount of quenching seen with a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…To overcome this problem, several methods have been developed to modify specifically the surfaces of polyolefinic films . They include grafting, layer-by-layer depositions, surface blending, and oxidations by plasmas, , corona discharges, flames, UV−vis irradiations, or chemicals . Polar groups physically or chemically attached to the film surfaces as a consequence of or subsequent to these modification procedures are usually very prone to loss in the environment by hydrolysis or contact with light and large concentrations of atmospheric oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, several methods have been developed to modify specifically the surfaces of polyolefinic films . They include grafting, layer-by-layer depositions, surface blending, and oxidations by plasmas, , corona discharges, flames, UV−vis irradiations, or chemicals . Polar groups physically or chemically attached to the film surfaces as a consequence of or subsequent to these modification procedures are usually very prone to loss in the environment by hydrolysis or contact with light and large concentrations of atmospheric oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…For several years now, our group has actively pursued the synthesis of functional surfaces through new grafting chemistry. Here we report the use of ultrathin grafted interfaces of poly(acrylic acid) or polyacrylamides on polyethylene and gold as substrates for hydrogen-bonded self-assembly. In this chemistry, a polyvalent hyperbranched hydrogen-bond donor or acceptor interface strongly adsorbs a polymeric hydrogen-bond acceptor or donor to prepare a functionalized interface that is stable to prolonged extraction with protic or aprotic solvents.…”
mentioning
confidence: 99%
“…In our prior work, we have shown that mixing terminally functionalized oligomers of ethylene with a large excess of a host polyethylene leads to “surface” functionalized polyethylene powder precipitates or solvent-cast films using the approach shown in Scheme . ,, …”
mentioning
confidence: 99%
“…In our prior work, we have shown that mixing terminally functionalized oligomers of ethylene with a large excess of a host polyethylene leads to "surface" functionalized polyethylene powder precipitates or solvent-cast films using the approach shown in Scheme 1. 1,10,11 Since this mixing approach to polyethylene functionalization is a general approach, we expected it to be applicable to other polyolefins including polypropylene. The ready availability of polypropylene oligomers with defined stereochemistry and terminal functionality has prompted us to test this hypothesis.…”
mentioning
confidence: 99%